Cytotoxicity assay of some plants from asteraceae - (:unkn) unknown (My University, 1998)
[No abstract available]
Keywords: Achillea vermicularis; Anthemis austriaca; Artemisia lamprocaulos; Centaurea behen; Centaurea kotschyi; Cytotoxicity; Sesquiterpene lactones